FLIPPING WRITING CLASSROOM AT SECONDARY SCHOOL: EFL STUDENTS' PERFORMANCE AND PERCEPTION - Destian, - (2019)
Recent phenomena indicates that teacher-centered learning still dominate the learning process in secondary education which conflicts with the constructivist approach to teaching and learning, especially in teaching writing skills. Based on the problem, this research was aimed to implement flipped classroom model in teaching writing skills for EFL students at secondary school because flipped classroom could create more student-centered learning. This research was aimed to find out the implementation of flipped classroom on EFL students' performance in writing skills and their perception toward flipped classroom. The research method was classroom action research that consisted of two cycles. The participants of the study were eleventh grade students. The data were collected through classroom observations, interviews, questionnaires, and document analysis. The research findings showed that the implementation of flipped classroom could help EFL students' performance in writing skills. The activities that could help them in composing cause and effect text were watching video lectures out-of-class, getting peer and teacher feedback, and performing quizzes. Majority of students showed their improvement of students' performance in three elements of writing skills, such as ideas and content, organization, and conventions. Moreover, this study also evidenced that most of students gave positive response toward flipped classroom.